Biomedical evaluation of green tea herbal liquid with bama miniature pigs - Yufan Li; Xinggang Zhao; Jun Liu; Mingyue Lin; Chenxin Wang; Rui Zhang; Li Chen; Qin Zou (Global Journal of Biotechnology and Biomaterial Science - Peertechz Publications, 2023)
Traditional Chinese Medicine (TCM) is widely used in health preservation and non-radical treatment because of its relatively gentle therapeutic effect, which is reflected in many products. Especially in atomization therapy, TCM shows its strong potential. This experiment focused on analyzing the extract of green tea (tea polyphenols) in a nebulizer, which is very similar to e-cigarettes. After intravenous injection of relevant drugs into small experimental pigs, the results of blood tests and the HE staining of organ sections showed no abnormalities in the experimental group. Since the dose of intravenous injection is much larger than that of nebulized inhalation, the safety of the product was verified by the experiment. The relevant analysis results obtained in this experiment will be used for comparison with subsequent, longer-term (more than 3 months) injection experiments.